2022
DOI: 10.1136/bmjopen-2021-054915
|View full text |Cite
|
Sign up to set email alerts
|

Physical and verbal abuse amid COVID-19: a nationwide cross-sectional survey in Japan

Abstract: ObjectivesThe detrimental impacts of abuse on victims’ well-being are well documented globally, including Japan. The ongoing COVID-19 pandemic may increase the incidence of abuse in the community, creating an additional burden amid the crisis. However, the incidence of abuse in Japan during COVID-19 remains to be evaluated. Accordingly, our study aimed to assess the incidence of physical and verbal abuse among the general population in Japan and to identify the associated factors of abuse during COVID-19.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, in Japan, high levels of stress, depression and anxiety were reported [25]. Increased rates of suicide and abuse were found, especially among young women [26,27]. Adolescent mental health was also a great concern and resilience was recommended as a coping strategy [28].…”
Section: Mental Health Difficulties In Non-weird Countriesmentioning
confidence: 99%
“…For example, in Japan, high levels of stress, depression and anxiety were reported [25]. Increased rates of suicide and abuse were found, especially among young women [26,27]. Adolescent mental health was also a great concern and resilience was recommended as a coping strategy [28].…”
Section: Mental Health Difficulties In Non-weird Countriesmentioning
confidence: 99%
“…The spread of coronavirus disease 2019 (COVID-19) has affected the worldwide (1)(2)(3). Although vaccines may not fully protect from the COVID-19, it is one of the most important public health interventions as the full range of vaccination among community people can help protect from transmission of infection from the infected to the uninfected and control potential death (4-9).…”
Section: Introductionmentioning
confidence: 99%
“…2,5 Previous studies note that COVID-19 restrictions have cultivated an environment in which perpetrators of DV exhibit tendencies of dominant control. 1,5 Bhandari et al 3 recently reported that physical abuse was associated with the state-of-emergency declaration in Japan. They further observed that the incidence of physical abuse was notably higher among female individuals, similar to observations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Pandemic-related restrictions have increased time spent in domestic settings and contributed to income instability for both perpetrators and survivors of DV . These living conditions affect households with potentially abusive individuals, with survivors of DV bearing most of the physical and mental health burden . We compared rates of incident DV inquiries during the COVID-19 pandemic with years before onset in Japan.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation